Controlled Attenuation Parameter for Quantification of Steatosis: Which Cut-Offs to Use? - Roxana Sirli; Ioan Sporea (Canadian Journal of Gastroenterology and Hepatology)
Chronic liver diseases (CLDs) are a public health problem, even if frequently they are underdiagnosed. Hepatic steatosis (HS), encountered not only in nonalcoholic fatty liver disease (NAFLD) but also in chronic viral hepatitis, alcoholic liver disease, etc., plays an important role in fibrosis progression, regardless of CLD etiology; thus, detection and quantification of HS are imperative. Controlled attenuation parameter (CAP) feature, implemented in the FibroScan® device, measures the attenuation of the US beam as it passes through the liver. It is a noninvasive technique, feasible and well accepted by patients, with lower costs than other diagnostic techniques, with acceptable accuracy for HS quantification. Multiple studies have been published regarding CAP performance to quantify steatosis, but due to the heterogeneity of CLD etiologies, of steatosis prevalence, etc., it had widely variable calculated cut-off values, which in turn limited the day-to-day utility of CAP measurements in clinical practice. This paper reviews published studies trying to suggest cut-off values usable in clinical practice.